2005
DOI: 10.1007/s00606-004-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the New World diploid cottons (Gossypium L., Malvaceae) based on sequences of three low-copy nuclear genes

Abstract: American diploid cottons (Gossypium L., subgenus Houzingenia Fryxell) form a monophyletic group of 13 species distributed mainly in western Mexico, extending into Arizona, Baja California, and with one disjunct species each in the Galapagos Islands and Peru. Prior phylogenetic analyses based on an alcohol dehydrogenase gene (AdhA) and nuclear ribosomal DNA indicated the need for additional data from other molecular markers to resolve phylogenetic relationships within this subgenus. Toward this end, we sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 34 publications
(84 reference statements)
8
38
0
Order By: Relevance
“…Among the 56 372 genes in the cotton assembly, an average of 47.5% were expressed in leaf tissue (Table 1). Notably, percentages were similar among the two D-genome diploids, as expected from their high genetic similarity (499% nucleotide identity in exons) (Alvarez et al, 2005). We also mapped the reads from D 5 onto the recently released D 5 -genome draft sequence to compare mapping efficiency; this resulted in 75% of reads mapping onto the 13 scaffolds of the draft assembly (Supplementary Table S2).…”
Section: Mapping Efficiency Of Rna-seq Datamentioning
confidence: 93%
“…Among the 56 372 genes in the cotton assembly, an average of 47.5% were expressed in leaf tissue (Table 1). Notably, percentages were similar among the two D-genome diploids, as expected from their high genetic similarity (499% nucleotide identity in exons) (Alvarez et al, 2005). We also mapped the reads from D 5 onto the recently released D 5 -genome draft sequence to compare mapping efficiency; this resulted in 75% of reads mapping onto the 13 scaffolds of the draft assembly (Supplementary Table S2).…”
Section: Mapping Efficiency Of Rna-seq Datamentioning
confidence: 93%
“…With respect to the D-genome half, the American diploid cottons (subgenus Houzingenia Fryxell) are a monophyletic group of 13 species located primarily in southwest Mexico and extending north into Arizona. Phylogenetic relationships among the species have been evaluated (Alvarez et al 2005), and previous research has identified Gossypium raimondii (D5) as the closest living relative of the paternal ancestor to all polyploid species using non-nuclear molecular methods and other evidence (Endrizzi et al 1985;Wendel and Cronn 2003). In the present study, we used sequence data from an intergenic region to explicitly test the relationship of D-genome species to all allopolyploids.…”
Section: Phylogenetic Inferences Of Monophylymentioning
confidence: 99%
“…The anticipated value of SNPs for analysis of candidate gene evolution and their eVects on complex traits have stimulated large scale SNP characterization and marker mapping in rice (Feltus et al 2004), wheat (Mochida et al 2003;Somers et al 2003;Zhang et al 2003;Caldwell et al 2004), maize (Ching et al 2002;Batley et al 2003), soybean Kim et al 2005), and barley (Kanazin et al 2002;Bundock et al 2003;Bundock and Henry 2004). Most cotton sequence variation analyses have been conWned to a single gene family or DNA fragments for phylogenetic analysis (Small et al 1998;Small and Wendel 2000;Cronn et al 2002;Alvarez et al 2005). Candidate gene-based association mapping using SNP markers has emerged as a powerful tool to determine the role of genes in complex traits (Glazier et al 2002).…”
Section: Introductionmentioning
confidence: 99%